2020
DOI: 10.4028/www.scientific.net/msf.1004.497
|View full text |Cite
|
Sign up to set email alerts
|

Defects Characterization of GaN Substrate with Hot Implant Process

Abstract: The defect structure of Mg implanted GaN substrate was evaluated by TEM observations, AFM surface observations and Raman scattering spectroscopic analysis. Mg ions were implanted at room temperature (RT) and 500 °C. TEM results showed that the defect distribution along depth scale is different between RT and 500 °C condition. The several peaks originated from ion implantation were found from Raman scattering spectra and the characteristics of the defects by implantation were discussed. The crystal quality of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…As a result, the crystalline distortion is removed. [ 23 ] From the TEM results, it is concluded that after annealing at 1040 °C, there is almost no shadow area in the region of 200 nm below the surface, which proves that the lattice damage was basically removed after 1040 °C annealing. And the relative stress change within the B region tends to level off with the increase of annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the crystalline distortion is removed. [ 23 ] From the TEM results, it is concluded that after annealing at 1040 °C, there is almost no shadow area in the region of 200 nm below the surface, which proves that the lattice damage was basically removed after 1040 °C annealing. And the relative stress change within the B region tends to level off with the increase of annealing temperature.…”
Section: Resultsmentioning
confidence: 99%
“…11) However, there have been only a few reports of channeled implantation of Mg ions to GaN. 11,[15][16][17] So far, we have evaluated the defects of GaN on sapphire induced by Mg random implantation using transmission electron microscopy (TEM), Raman spectroscopy and atomic force microscopy (AFM), 18) but the defects of Mg channel implanted layers have not been evaluated fully. In this work, we confirmed the activation of Mg and evaluated Mg channel implanted layers.…”
Section: Introductionmentioning
confidence: 99%